Agent‐Based Modeling in Systems Pharmacology. (13th November 2015) - Cosgrove, J; Butler, J; Alden, K; Read, M; Kumar, V; Cucurull‐Sanchez, L; Timmis, J; Coles, M
Abstract : Modeling and simulation (M&S) techniques provide a platform for knowledge integration and hypothesis testing to gain insights into biological systems that would not be possible a priori . Agent‐based modeling (ABM) is an M&S technique that focuses on describing individual components rather than homogenous populations. This tutorial introduces ABM to systems pharmacologists, using relevant case studies to highlight how ABM‐specific strengths have yielded success in the area of preclinical mechanistic modeling.